Focus characterization of the NanoMAX Kirkpatrick–Baez mirror system. (11th June 2019) - Osterhoff, Markus; Robisch, Anna-Lena; Soltau, Jakob; Eckermann, Marina; Kalbfleisch, Sebastian; Carbone, Dina; Johansson, Ulf; Salditt, Tim
Abstract : Using an X‐ray waveguide, the focal spot size and coherence properties of the NanoMAX Kirkpatrick–Baez mirror system have been measured. Abstract : The focusing and coherence properties of the NanoMAX Kirkpatrick–Baez mirror system at the fourth‐generation MAX IV synchrotron in Lund have been characterized. The direct measurement of nano‐focused X‐ray beams is possible by scanning of an X‐ray waveguide, serving basically as an ultra‐thin slit. In quasi‐coherent operation, beam sizes of down to 56 nm (FWHM, horizontal direction) can be achieved. Comparing measured Airy‐like fringe patterns with simulations, the degree of coherence |μ| has been quantified as a function of the secondary source aperture (SSA); the coherence is larger than 50% for SSA sizes below 11 µm at hard X‐ray energies of 14 keV. For an SSA size of 5 µm, the degree of coherence has been determined to be 87%.